Problems and Approaches to Increase the Cybersecurity Level in the Data Transmission Channels of the Internet of Things Systems and Devices - Malinovskyi , V. І.; Kupershtein, L. М.; Lukichov, V. V.; Dudat’ev, A. V. (Visnyk of Vinnytsia Politechnical Institute, 2024)
The article deals with modern technologies and devices of the Internet of Things, features of providing their cybersecurity, current risks and the latest and effective approaches to high-level cyber defense in the architecture of the Internet of things. The problems of cyber threats in modern internet devices are diverse and generate a significant problem on the path of further promotion of IoT technologies. These are various and complex information risks of cybersecurity for processing and transmission processes in the IoT structures and devices that use different technologies of intervention in the main functionality. As the IoT devices and systems use the Internet and interfaces of the Internet, as well as wireless radio interfaces in combination with mobile operating systems based on high -yielding ARM processors, the risks of IoT cybersecurity are growing significantly and put in question the long -term stable functioning of IoT systems. Sometimes these risks of cybersecurity create a significant problem for information data in IoT systems, and significantly slow down their promotion in a number of industries. Therefore, this problem must be resolved. The work has evaluated and analyzed the problems of cybersecurity in the IoT, the existing approaches are considered and new effective practical provisions and approaches to ensure high cyber defense systems and Internet devices are suggested . The aspects have been considered and the analysis of the problems of cybersecurity of the Internet of things using approaches and methods of the improved protection of data transmission in systems and channels of the Internet of things that are connected to modern Internet information network is carried out. Approaches to more protected data transmission in IoTs, based on a comprehensive combination of known technologies with a combination of their aggregate use and symbiosis with other technologies, are proposed. This enables to enhance cybersecurity and reduce the risks of cyber threats in IoT systems that occur and also takes place in other modern information systems that are often connected and guided via the Internet. These approaches and principles allow to increase the reliability and overall protection of data transmission to IoT, evaluate the main factors of the impact of information threats and to reduce the consequences of their implementation. The prospects for the development of these approaches and methods in complex IoT data exchange systems are considered. The advantages of the method and approaches of cyber defense while the transmission of data to IoT and protected cryptographic processing and transmission of information in the devices and information systems of the Internet of things are described.